Silica Supported Bimetallic Catalysts for Liquid Phase Selective Hydrogenation of Citral - Ananthan*, S.A.; Narayanan, V. (Asian Journal of Chemistry, 2011)
Three series of bimetallic catalysts Co-Ni, Ni-Cu and Cu-Co in silica supported were prepared by deposition precipitation method and calcined at 773 and 923 K. The prepared catalysts were investigated by BET surface area, XRD, thermogravimetry, EDX, SEM and FTIR techniques. The XRD measurements reveal formation of a specific solid solution in the case of Co-Ni/SiO2 and Cu-Co/SiO2 catalysts. However, in the case of Ni-Cu/SiO2 catalyst only peaks due to CuO and NiO were observed. The SEM measurements suggest that the prepared bimetallic catalysts are in a highly dispersed form over the surface of the colloidal silica support. These catalysts were evaluated for liquid phase selective hydrogenation of citral to unsaturated alcohols under ranges of temperature, pressure and loading of catalyst. Among these catalysts investigated, the 773 K calcined Co-Ni/SiO2 catalyst exhibited a high conversion in a isopropanol as a solvent medium, the maximum selectivity of geraniol and nerol obtained by 363 K temperature, 4 bar pressure, 0.2 % w/v catalyst load with 750 rpm agitation.